PIV measurement of separated flow in a square channel with streamwise periodic ribs on one wall - Wang, Lei; Hejcik, J.; Sundén, Bengt (Journal of Fluids Engineering, 2007)
In. this study, particle image velocimetry (PIV) is used to investigate the physical process of separated flow in a square channel roughened with periodically transverse ribs on one wall. The ribs obstruct the channel by 15% of its height and are arranged 12 rib heights apart. The Reynolds number based on the bulk-mean velocity and the corresponding hydraulic diameter of the channel, is fixed at 22,000. Assuming flow periodicity in the streamwise direction, the investigated domain is between two consecutive ribs. The emphasis of this study is to give some insight into the turbulence mechanism associated with separation, reattachment, and subsequent redevelopment. Results are included for mean velocity, friction coefficient, vorticity thickness, Reynolds shear stress, anisotropy parameter and production of turbulent kinetic energy and shear stress. Based on the two-point correlation profiles, Taylor microscales are derived to reveal the sizes of the turbulence structure in the longitudinal and lateral directions. Moreover Galilean decomposition is applied to the instantaneous velocity fields. The result shows that the separated shear layer is dominated by the large-scale, unsteady vortical structures.
Keywords: PIV; turbulence properties; separated flow